SOCIAL INCLUSION OF INDIVIDUALS SUFFERING FROM EXCLUSION – EVALUATION OF MOTIVES AND ACTIONS IN VIEW OF OWN RESEARCH - Mariola Szewczyk-Jarocka (Acta Scientiarum Polonorum. Oeconomia, 2019)
Main aim of analyses presented in the article was to determine the motives and actions which promote social inclusion of the unemployed, most frequently suffering from social exclusion. The survey was conducted in 2018 based on the questionnaire among the population of 350 respondents. The analyses included the distribution of answers to survey question within the entire sample together with the verification of statistical significance between the answers provided and such variables as: gender, age, education and period of being registered in Municipal Employment Office. Results of the study show that increasing social awareness on the access to benefits is an important motif influencing social inclusion. The awareness of the fact of being deprived of the right to retirement pension, no access to healthcare and increased creditworthiness shape the knowledge of the society in relation to the importance of working within the official labour market to a significant extent.